Políticas públicas para mulheres: implementação e desafios ao enfrentamento da violência no município de São Carlos - Leandro, Amaranta Ursula Fiess (2014)
The present work analyses the public policies related to confronting violence against women in São Carlos city, between 2008 and 2012, from the field research carried out along with various bodies responsible for their implementation in a local sphere, regardless of being associated with the federal, state or municipal sphere of the government. The bodies are: Center of Reference for women (CRM), Women Police Station (DDM), public defender, Care Program for Women Victims of Sexual Violence (PAVAS) and Laboratory of Analysis and Prevention of Violence (LAPREV). From the documents and interviews carried out with representatives from two of these bodies, the research tried to respond: a) if the actions taken by them are based on the National Policy for Confronting the Violence against Women and Maria da Penha Law; b) which means, strategies and difficulties were found for taking such actions; and c) if there is an interconnected network in federal and intersectoral terms for the integral assistance to women victims of violence in São Carlos. The study attempts to rescue the history and reflection about the appearance of human rights, as well as the struggle of women s movements to recognize and guarantee their interests, freedom and rights, with an approach based on feminism, gender issues and the recognition of the violence against women as a public problem, which resulted in the development of the public policies for women both in international and national sphere. It was concluded that there has been a recent empowerment of these policies in Brazil through the development of law and institutional tools that broadened and directed the protective measures for women. In the case of São Carlos city, they also contributed to the local management course and initiatives, associated with the commitment to the cause, and enabled the creation of a service network integrated with all the bodies and services, although its growth, allied to a civil education of respect to women, consists of challenges to be faced in the management and implementation of more efficient policies to combat violence against women in the city.